THE USE OF CODED FEEDBACK TO ENHANCE THE LEARNERS’ AWARENESS AND ACCURACY IN EFL WRITING - Eko Windu Prasetya (Universitas Bandar Lampung, 2019)
To many scholars, error correction plays a significant role in improving learners’ accuracy in language learning especially in EFL writing, which is grammatically demanding. In terms of teachers’ roles in giving correction, the popular misunderstanding overemphasizes teachers’ responsibility in carrying out the task while ignoring learners’ roles in the process of error correction. Accordingly, this paper aims to signify the advantages of coded feedback in relation to the development of EFL learners’ writing skill. Notwithstanding coded feedback’s requiring learners’ autonomy during the error correction process, the method offers a challenging and stimulating way of error correction in writing. This paper will cover the characteristics of coded feedback and its benefits towards the learners’ writing skill development.